17 Help wanted: identifying and addressing sexual distress in newly referred gynecologic oncology patients - Allyson Jang; Leah Wormack; Anjali Walia; Tami Rowen; Lee-may Chen (Elsevier, 2023)
Objectives: To assess predictors of help-seeking for sexual distress in a cohort of patients newly referred to a gynecologic oncology clinic Methods: We performed a cross-sectional study of new patients referred to a gynecologic oncology clinic for a known or suspected gynecologic malignancy. Our primary outcome was sexually related distress, classified as a score of 11 or above using the validated Female Sexual Distress Survey-Revised (FSDS-R). The PROMIS Female Sexual Function and Satisfaction Questionnaire (SexSF) is a validated instrument examining domains of sexual function over the past 30 days. We performed one-sided t-test and logistic regression statistical analyses using STATA version 17.0. Results: From May-Dec 2022, 105 of 126 (83%) eligible patients completed the survey. The median age of respondents was 60.5 years old (range 26-85). 48% of patients had a known cancer diagnosis at the time of their visit, with 71% percent having cancer confirmed on final pathology (25% ovarian, 49% uterine, and 19% cervical/vaginal/ vulvar). 50% of patients self-identified as non-Hispanic White, and 50% were non-White (Black, Asian, Pacific Islander, and Latinx), and 6% were LGBTQ. 37.5% reported being sexually active within the past 30 days. FSDS-R scores ranged from 0-32 with a median (IQR) of 2.5 (9.5). Overall, 23% of this cohort reported sexually related distress. This was not significantly associated with cancer diagnosis on arrival, final diagnosis, site of origin, or with sexual activity. 53% of patients agreed that physicians should routinely ask about sexual function. 37% of patients desired to speak with their gynecologic oncologist about sexual health, the majority (64%) of whom did not have sexual distress. Additionally, 27% desired referral to sexual health specialists, psychologists or counselor regarding sexual health concerns. Conclusions: Almost a quarter of new patients to gynecologic oncology clinic reported sexually related distress. A majority preferred to speak to their gynecologic oncologist regarding sexual health, regardless of personal report of sexual distress. Gynecologic oncology providers should incorporate screening for sexual symptoms into evaluation and treatment planning.